Experimental systems to study the origin of the myofibroblast in peritoneal fibrosis - Manreet Padwal; Peter J. Margetts (The Korean Society of Nephrology, 2016)
Peritoneal fibrosis is one of the major complications occurring in long-term peritoneal dialysis patients as a result of injury. Peritoneal fibrosis is characterized by submesothelial thickening and fibrosis which is associated with a decline in peritoneal membrane function. The myofibroblast has been identified as the key player involved in the development and progression of peritoneal fibrosis. Activation of the myofibroblast is correlated with expansion of the extracellular matrix and changes in peritoneal membrane integrity. Over the years, epithelial to mesenchymal transition (EMT) has been accepted as the predominant source of the myofibroblast. Peritoneal mesothelial cells have been described to undergo EMT in response to injury. Several animal and in vitro studies support the role of EMT in peritoneal fibrosis; however, emerging evidence from genetic fate-mapping studies has demonstrated that myofibroblasts may be arising from resident fibroblasts and pericytes/perivascular fibroblasts. In this review, we will discuss hypotheses currently surrounding the origin of the myofibroblast and highlight the experimental systems predominantly being used to investigate this.